1990
DOI: 10.1164/ajrccm/141.5_pt_1.1096
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography to Stage Lung Cancer: Approaching a Controversy Using Meta-analysis

Abstract: The ability of computed tomography (CT) to detect mediastinal lymph node metastases from nonsmall cell bronchogenic lung cancer is highly controversial, as evidenced by reported accuracies ranging from 0.35 to 0.95 over the past eight years. We examined all studies on this matter published between January 1980 and April 1988, both to describe the overall experience and to identify characteristics (study design and methodology and CT scan techniques) that influenced reported accuracy. Of 79 relevant publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(53 citation statements)
references
References 16 publications
1
51
0
1
Order By: Relevance
“…In 1988 STAPLES et al [106] demonstrated 79% sensitivity and 65% specificity for CT using a 1-cm long axis nodal cut-off measurement. A meta-analysis in 1990 of 42 CT studies assessing mediastinal lymph node metastases from NSCLC described an overall sensitivity of 0.79, a specificity of 0.78 and an accuracy of 0.79 [107]. However, in 1992 MCLOUD et al [108] using a nodal short axis measurement of 1 cm in 143 patients, returned to less inspiring figures of 64% sensitivity and 62% specificity, respectively.…”
Section: Nodal Statusmentioning
confidence: 99%
“…In 1988 STAPLES et al [106] demonstrated 79% sensitivity and 65% specificity for CT using a 1-cm long axis nodal cut-off measurement. A meta-analysis in 1990 of 42 CT studies assessing mediastinal lymph node metastases from NSCLC described an overall sensitivity of 0.79, a specificity of 0.78 and an accuracy of 0.79 [107]. However, in 1992 MCLOUD et al [108] using a nodal short axis measurement of 1 cm in 143 patients, returned to less inspiring figures of 64% sensitivity and 62% specificity, respectively.…”
Section: Nodal Statusmentioning
confidence: 99%
“…51 A classic meta-analytic review of 42 early studies documented, on average, a CT accuracy rate of 80%. 52 Recent estimates suggest more prudent figures, in the 50 -60% range in the United States and in the 60 -70% range in Europe and Japan. 53,54 According to these last data, thoracic CT might be insufficiently accurate for being the ideal preoperative staging test.…”
Section: Discussionmentioning
confidence: 99%
“…were necessarily based on endoscopic and/or radiological criteria. Although these criteria are useful for daily clinical practice, the cytohistological diagnosis of cN1–2 should be considered the criterion of classificatory certainty in view of the operational characteristics of CT for mediastinal lymph nodes (sensitivity 0.79 and specificity 0.78 in meta-analytical studies [10]).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, radiographic detection of the destruction of a vertebral body has a high level of classificatory certainty. For cN categories, radiological methods may suggest tumoral involvement (using the latest-generation CT scanners), but do not have an acceptable classificatory certainty [10]. …”
Section: Introductionmentioning
confidence: 99%